Pitch Correction - ett måste? En intervjuundersökning om åsikter kring användning av pitch correction i dagens musikskapande. - Gustavsson,Caroline (2008)
Pitch Correction - is it a must? An interview inquiry about opinions concerning pitch correction in music making today. This work intends to find out what music producers, singers and those with a great interest in music really think about the use of pitch correction programs, both in the studio and live. The thoughts concerning this came when I began to work with these programs in a studio, mostly for vocal use. I realized that the thoughts and opinions about the use of pitch correction varies a lot. Later my thoughts formed a research question: What are the opinions among music producers, singers and listeners concerning pitch correction? In my study I have interviewed three professionally educated music teachers. The first one works as a music producer/singer, the second one as a singer/voice coach and the third one works as a music teacher and is also active as a studio musician on his spare time. All my informers listen to a lot of music. The results show that the use of pitch correction programs is mostly a matter of genre and taste. Using it in the studio seems however to be more accepted than using it live. There are many thoughts considering whether pitch correction is used just to help those who cannot sing and if it is used mostly as an effect or to enhance the sound in a certain genre. One of my conclusions is that there is still a lot of talent and a lot of hard work involved in the process of making music regardless of technical developments like pitch correction. Detta arbete syftar till att ta reda på vad musikproducenter, sångare/sångerskor och musikintresserade egentligen tycker om användandet av pitch correction program, både i studio och live. Mina funderingar kring detta dök upp när jag började jobba med dessa program i studio, främst inom sång. Jag upptäckte att tankarna och uppfattningarna kring användandet av pitch correction varierar en hel del. Mina tankar kom senare att bli min frågeställning: Vilka uppfattningar finns bland musikproducenter, sångare/sångerskor och lyssnare om pitch correction? I min undersökning har jag intervjuat tre professionellt utbildade musiklärare. Den första arbetar som musikproducent/sångare, den andra är verksam som sångerska/sångpedagog och den tredje arbetar som musiklärare men är på sin fritid verksam som studiomusiker. Alla mina informanter lyssnar oerhört mycket på musik. Resultatet av mina studier visar att pitch correction till stor del handlar om genre och smak. Användandet i studio verkar dock vara mer accepterat än användandet i livesammanhang. Det finns många tankar kring huruvida pitch correction endast är till för att hjälpa/rädda de som inte kan sjunga eller om det används mest som en effekt eller för att få rätt sound i en specifik genre. En av mina slutsatser är att det fortfarande krävs och är mycket talang och hårt arbete inblandat i processen av musikskapande oberoende av om man använder tekniska hjälpmedel som pitch correction eller ej.
Keywords: autotune; melodyne; pitch correction; Musicology; Musikvetenskap; Pedagogy and didactics; Pedagogik, didaktik